Electrical and thermal transport properties of medium-entropy SiyGeySnx alloys. (15th October 2020) - Wang, Duo; Liu, Lei; Chen, Mohan; Zhuang, Houlong
Abstract: Electrical and thermal transport properties of disordered materials have long been of both theoretical interest and engineering importance. As a new class of materials with an intrinsic compositional disorder, high/medium-entropy alloys (HEAs/MEAs) are being immensely studied mainly for their excellent mechanical properties. By contrast, electrical and thermal transport properties of HEAs/MEAs are less well studied. Here we investigate these two properties of silicon (Si)-germanium (Ge)-tin (Sn) MEAs, where we keep the same content of Si and Ge while increasing the content of Sn from 0 to 1/3 to tune the configurational entropy and thus the degree of compositional disorder. We predict all Si y Ge y Sn x MEAs to be semiconductors with a wide range of band gaps from near-infrared (0.28 eV) to visible (1.11 eV) in the light spectrum. We find that the band gaps and effective carrier masses decrease with increasing Sn content. As a result, increasing the compositional disorder in Si y Ge y Sn x MEAs enhances their electrical conductivity. For the thermal transport properties of Si y Ge y Sn x MEAs, our molecular dynamics simulations show an opposite trend in the thermal conductivity of these MEAs at room temperature, which decreases with increasing compositional disorder, owing to enhanced Anderson localization and strong phonon-phonon anharmonic interactions. The enhanced electrical conductivity and weakened thermal conductivity make Si y Ge y Sn x MEAs with high Sn content promising functional materials for thermoelectric applications. Our work demonstrates that HEAs/MEAs not only represent a new class of structural alloys but also a novel category of functional alloys with unique electrical and thermal transport properties. Graphical abstract: Graphical abstract Image, graphical abstract